(untitled) (Research, Society and Development, 2022)
The research aimed to evaluate the knowledge of medical students from the University Center FAMINAS, located in the city of Muriaé, in the state of Minas Gerais, regarding aspects related to oral health and its systemic implications, and then present a literature review on its relevance and aspects. The answers of medical students obtained through a structured questionnaire produced using the Google Forms platform and sent via social network and e-mail to the undergraduates of the course in question were delimited as a sample. Then, the data were tabulated in Microsoft Excel spreadsheets and used for the analysis and conclusion of the research. It was concluded that medical students understand the relevance of the subject studied, as well as the importance of hospital dentistry and the presence of a dentist within the hospital. However, there are some gaps to be improved.